Evaluation of inbred lines of baby corn through line × tester method - Ahmed, A; Begum, S; Omy, SH; Rohman, MM; Amiruzzaman, M (Bangladesh Journal of Agricultural Research, 2016)
Seven lines of baby corn were crossed with 3 testers in a Line × Tester (L × T) mating design and the resulting 21 crosses along with parents and standard check Baby Star were evaluated to develop high yielding baby corn hybrids during rabi, 2014-15. Variance due to sca was larger than gca variance for all the characters indicating the preponderance of non additive gene action in the expression of various traits. Among the parents, BCP/S4-29, BCP/S4-31 and tester VS/S3-1 and VS/S3-26 were found as good general combiners for baby corn yield and important yield contributing characters. Considering baby corn yield, number of cobs/plant and other performances, the crosses BCP/S4- 2×VS/S3-1, BCP/S4-5×VS/S3-8, BCP/S4-10×VS/S3-8, BCP/S4-22×VS/S3-26 and BCP/S4-29×VS/S3-1 were selected as promising baby corn hybrids. Bangladesh J. Agril. Res. 41(2): 311-321, June 2016